Portraits from the French Renaissance and the Wars of Religion - Thevet, André, 1502-1590 (Early modern studies series, 2010)
Available for the first time in English, these thirteen selections from André Thevet's Les vrais pourtraits et vies des hommes illustres offer a glimpse of France during a time of great upheaval. Originally published in 1584, Thevet's collection contains over two hundred biographical sketches, detailing the lives of important persons from antiquity to the sixteenth century. Edward Benson and Roger Schlesinger have translated and annotated Thevet's portraits of his contemporaries, and divided them into three categories: monarchs, aristocrats, and scholars. Additionally, an extensive introduction places the work in context and describes the critical attention that Thevet and his writings have received. Together these portraits provide a history of sixteenth-century France as the country underwent tremendous change: from an intellectual renaissance and its first encounter with the New World to the Protestant Reformation and the Wars of Religion that followed. France was irrevocably altered by these events and Thevet's account of the lives of individuals who struggled with them is indispensable.--